2016
DOI: 10.1017/s1041610216000788
|View full text |Cite
|
Sign up to set email alerts
|

Do not hear, see, or speak: views of older residents and their adult children about the nursing unit in the continuing care retirement community

Abstract: The findings point to the ambivalence expressed by CCRC residents and their adult children concerning the NU, even though to some degree, the NU represents the main reason for the transition to a CCRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Contrary to our expectations, demographic variables, health, and subjective social location did not play consistent roles in determining the presence of close ties between individuals. This finding is surprising given past research that emphasized the role of CCRC residents’ health in the presence of close social ties [62], as health is a scarce resource in the CCRC [9, 25]. Other demographic and subjective social position characteristics also did not have a consistent role in determining the presence of social ties.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Contrary to our expectations, demographic variables, health, and subjective social location did not play consistent roles in determining the presence of close ties between individuals. This finding is surprising given past research that emphasized the role of CCRC residents’ health in the presence of close social ties [62], as health is a scarce resource in the CCRC [9, 25]. Other demographic and subjective social position characteristics also did not have a consistent role in determining the presence of social ties.…”
Section: Discussionmentioning
confidence: 67%
“…Consistently, a higher level of cognitive functioning has also been shown to be associated with a larger social network [27, 28]. These findings obtained from an analysis of the entire social network of CCRC residents are supported by qualitative research that has identified physical and cognitive functioning as valuable assets of CCRC residents [9, 25, 29].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…While their health condition remained the same through the year, they probably were exposed to other older adults with poorer health conditions. While the presence of older adults with poor health can be bothersome (Ayalon, 2016), this could also lead to a positive result, as older adults tend to rate their health based on their comparisons to others (Smith and Goldman, 2011). This comparison could serve as evidence supporting their decision to move, thereby increasing satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of settings was fueled by past research ( Ayalon & Green, 2015 ; Ayalon, 2016b ), which has stressed the importance of the CCRC’s features in shaping older residents’ social lives. In selecting the settings, we specifically aimed for geographic diversity (center, south, Jerusalem) as well as for variations in size (40–299), socioeconomic status and cultural background.…”
Section: Methodsmentioning
confidence: 99%